The moderating effect of selling prices and buying prices on the effect of copper hedging on the profitability of the copper division of PT. TMS - Sylvia Yulyanti; Rudolf Lumbantobing (Institute of Computer Science (IOCS), 2023)
Profitability is a major factor that determines the survival of a company. There are two general factors to determine the profitability of a company, namely first sales and second direct and indirect costs. However, there are other factors that affect the profitability of the company itself, namely hedging activities. The company in this study is PT. Tembaga Mulia Semanan Tbk. ( PT. TMS ), a manufacturing company that produces copper wire & rod. This study has three objectives, namely to determine the effect of hedge metal on profitability, and identify whether the selling price or purchase price can moderate this influence on company profitability. This study uses the type of data Secondary data taken directly from PT. Tembaga Mulia Semanan Tbk. In addition, this research is also supported by literature research through literature books and journals. The population data at PT. Tembaga Mulia Semanan Tbk. as much as 700 data. In this study, the authors used simple random sampling, the number of samples to be taken in this study was 240 data (monthly data from 2016 – 2021. This study uses multiple regression analysis with moderation, below is the regression model. Based on the results of the study, empirical facts were obtained in the form of: 1) 1. Hedge Amount has a significantly negative effect on EBIT; 2) The negative effect of the Hedge Amount on EBIT will be more positive when the Selling Price increases; 3) Purchase Price significantly moderates the positive effect of Hedge Amount on EBIT.